Neonatal morbidity after fetal exposure to antipsychotics: a national register-based study. Issue 6 (29th June 2022) - Heinonen, Essi; Forsberg, Lisa; Nörby, Ulrika; Wide, Katarina; Källén, Karin
Abstract : Objective: To investigate the admission rate to neonatal care and neonatal morbidity after maternal use of antipsychotics during pregnancy. Design: A population-based register study. Setting: Information on all singleton births between July 2006 and December 2017 in Sweden including data on prescription drugs, deliveries and infants' health was obtained from the Swedish Medical Birth Register, the Prescribed Drug Register and the Swedish Neonatal Quality Register. Exposed infants were compared with unexposed infants and with infants to mothers treated with antipsychotics before or after but not during pregnancy. Participants: The cohort comprised a total of 1 307 487 infants, of whom 2677 (0.2%) were exposed to antipsychotics during pregnancy and 34 492 (2.6%) had mothers who were treated before/after the pregnancy. Outcome measures: The primary outcome was admission rate to neonatal care. Secondary outcomes were the separate neonatal morbidities. Results: Of the exposed infants, 516 (19.3%) were admitted to neonatal care compared with 98 976 (7.8%) of the unexposed infants (adjusted risk ratio (aRR): 1.7; 95% CI: 1.6 to 1.8), with a further increased risk after exposure in late pregnancy. The highest relative risks were seen for withdrawal symptoms (aRR: 17.7; 95% CI: 9.6 to 32.6), neurological disorders (aRR: 3.4; 95% CI: 2.4 to 5.7) and persistent pulmonary hypertension (aRR: 2.1; 95% CI: 1.4 to 3.1) when compared with unexposed infants. The absolute risks for these outcomes were however low among the exposed infants, 1.3%, 1.8% and 1.0%, respectively, and the relative risks were lower when compared with infants to mothers treated before/after the pregnancy. Conclusion: Fetal exposure to antipsychotics was associated with an increased risk of neonatal morbidity. The effects in the exposed infants seem transient and predominantly mild, and these findings do not warrant discontinuation of a necessary treatment but rather increased monitoring of these infants. The increased risk of persistent pulmonary hypertension requires further studies.